Improving the Passengers' Facilitation: Karachi, Lahore, and Islamabad Airports - Baig, Faisal Ishfaq (Journal of Pakistan Administration, 2024)
In 2023, out of 19.64 million passengers that travelled from Pakistani airports, 16.64 million passengers traveled from Karachi, Lahore and Islamabad airports. Despite accommodating more than 2/3rd air passengers, the standard of facilitation is deplorable. In 2014, Islamabad airport was declared world’s worst airport and in 2022, performance of Pakistani airports was marked 0.3 %. In recent surveys, 62% of passengers showed dissatisfaction with the amenities, 27 % found them satisfactory while only 10% declared them Good. 12.31% of passengers found the handling and treatment of airport functionaries as Good. 39.36 % were satisfied whereas 48.65 % passengers termed them unsatisfactory. Although, Pakistan has adopted legal frameworks in form of Air Navigation Order 2015- Air Passenger Rights and CAA Regulations 2018- Facilitation in line with ICAO (Annex A), however, it is the non-implementation of these that has led to poor passenger experiences. The major reason behind the non-implementation is the dual role of PCAA as service provider and regulator which is against the international practices and is conflict of interest. PCAA has badly neglected its role and task of being the Regulator. To address this important issue, Govt. of Pakistan passed two separate bills in 2023 to bifurcate PCAA as service provider and regulator. However, after a hiatus of one year in 2024, PCAA was merely announced to be split in service provider and regulator. Likewise, there is lack of monitoring and supervision of performance of staff of different agencies like Pakistan Customs, ANF, FIA and ASF, resultantly the staff concerned deal the passengers in discourteous and annoying manner.Keywords: , , ,
Keywords: Lack of facilitation; Major Pakistani Airports; Role of stakeholder; Implementation of legal framework